2021
DOI: 10.3390/ijerph182111066
|View full text |Cite
|
Sign up to set email alerts
|

Distress Levels of Parents of Children with Neurodevelopmental Disorders during the COVID-19 Pandemic: A Comparison between Italy and Australia

Abstract: Parents of children with a neurodevelopmental disorder (NDD) report higher levels of distress compared to those of typically developing children. Distress levels may be heightened by the restrictions associated with the COVID-19 pandemic. However, it is unclear whether distress levels of parents varied by the diagnosis of neurodevelopmental disorder in children during the COVID-19 pandemic. This study aims to investigate whether parental distress was influenced by the type of NDD. Participants were from Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Other frequently reported effects on families were that parents felt constrained to allow excessive media use in the absence of other leisure activities, multiple burdens imposed by pandemic restrictions especially on mothers, and parents feeling overwhelmed by the supervision of homeschooling tasks. The burden experienced by mothers under COVID-19 has been reported in the literature (Calvano et al 2021 ; McLaren et al 2020 ; Taylor et al 2021 ), and mothers of children with depression or developmental disorders are known to be under extra strain (Babore et al 2021 ; Burnett et al 2021 ; Chafouleas and Iovino 2021 ; Wang et al 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…Other frequently reported effects on families were that parents felt constrained to allow excessive media use in the absence of other leisure activities, multiple burdens imposed by pandemic restrictions especially on mothers, and parents feeling overwhelmed by the supervision of homeschooling tasks. The burden experienced by mothers under COVID-19 has been reported in the literature (Calvano et al 2021 ; McLaren et al 2020 ; Taylor et al 2021 ), and mothers of children with depression or developmental disorders are known to be under extra strain (Babore et al 2021 ; Burnett et al 2021 ; Chafouleas and Iovino 2021 ; Wang et al 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…It seems to be the same for children, and the study by Ehrler et al (2021) indicates that the parents of children with congenital heart disease were reported to be more concerned about becoming infected with SARS-CoV-2 than others. It would be interesting to specify in a later study whether there is a significant differentiation between the types of disorders (i.e., intellectual, physical disorders) or diseases in children whose parents feel more affected and have adopted these social distancing measures more than others, as was done by Burnett et al (2021) regarding the level of distress among parents in Australia and Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed a significant increase in parental stress and children externalising behaviours, but not in co-parenting, although they did not distinguish between families of very young children and others. Results from Burnett et al (2021) also showed higher levels of distress for parents of children with a neurodevelopmental disorder compared to those of typically developing children. However, once again the children in the study were over 3 years old and from Australian and Italian populations.…”
Section: Introductionmentioning
confidence: 92%
“…The negative impact of the pandemic and associated preventative measures on the quality of life and mental health of people in the general population has received much attention in research (e.g., Epifanio et al, 2021 ; Passavanti et al, 2021 ; Pieh et al, 2020 ; Xiong et al, 2020 ). Relatives of individuals with intellectual disabilities might be disproportionately affected by the pandemic (Burnett et al, 2021 ; Grumi et al, 2020 ; Mak et al, 2021 ). In line with this, a study by Willner et al ( 2020 ) during the lockdown showed that relatives of people with intellectual disabilities reported significantly higher levels of anxiety, depression and defeat than relatives of people without intellectual disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the experiences of relatives and the impact of the pandemic on mental health outcomes of relatives such as stress, depression, and anxiety (Asbury et al, 2021 ; Burnett et al, 2021 ; Linehan et al, 2022 ; Redquest et al, 2021 ; Rogers et al, 2021 ; Willner et al, 2020 ). Less is known about the impact on their quality of life.…”
Section: Introductionmentioning
confidence: 99%